Stakeholders Approach for Medicinal Plants Cultivation : a Case Study from Tamil Nadu - Debnath, D. (Indian Forester, 2009)
India is recognised as one of the countries having the oldest, richest and most diverse cultural traditions associated with the use of herbal medicines. But due to over-harvesting in their natural habitats, many medicinal plants have been put on the endangered list of IUCN. These can not be exported from India, though the Planning Commission, Govt. of India, has set up plans to increase trade in medicinal plants extracts. Hence, cultivation is preferable to in-situ conservation, as recommended by National Medicinal Plants Board and simultaneously the dissemination of knowledge for trade for the livelihood security of the Indian ruralites. The Tamil Nadu experiment in Vellore Forest Division in the Vellore District has developed a model of stakeholders approach for cultivating the medicinal plants. This is an outcome of the Tamil Nadu Afforestation Project (TAP), sponsored by Japan Bank for International Cooperation (JBIC). This is a collaborative effort of a traditional Sidda Practitioner, the Forest Department and the local communities. Beginning from awareness development towards the benefits of the herbal medicines by the local medicinal practitioners, development of the medicinal plants garden, to the involvement of Self-Help groups for planting the medicinal plants in their kitchen garden and homestead land for their livelihoods promotion. This paper attempts to develop a model through various stakeholders for cultivation of medicinal plants.